2018
DOI: 10.1002/jso.25351
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on image‐guided navigation surgery for pelvic malignancies

Abstract: Background and objectives Surgery of advanced tumors and lymph nodes in the pelvis can be challenging due to the narrow pelvic space and vital surrounding structures. This study explores the application of a novel electromagnetic navigation system to guide pelvic surgery. Methods This was a prospective study on surgery for malignancies in the pelvis. Preoperatively obtained imaging was used to create a patient‐specific three‐dimensional (3D) roadmap. In the operating room, the 3D roadmap was registered to an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 21 publications
3
49
1
Order By: Relevance
“…One study tested image-guided navigation in a large group. 13 Outcomes of this pilot study were encouraging, showing the navigation system was safe, feasible, and accurate (mean target registration error: 4.0 mm). However, the study included a wide variety of pelvic tumors and mainly focused on the feasibility and accuracy of the navigation system.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…One study tested image-guided navigation in a large group. 13 Outcomes of this pilot study were encouraging, showing the navigation system was safe, feasible, and accurate (mean target registration error: 4.0 mm). However, the study included a wide variety of pelvic tumors and mainly focused on the feasibility and accuracy of the navigation system.…”
Section: Discussionmentioning
confidence: 81%
“…Image-guided navigation in pelvic surgical procedures has been described previously. 13 , 16 , 17 , 18 , 19 Two separate groups investigated the feasibility of navigation in pilot studies for Transanal Minimal Invasive Surgery–Total Mesorectal Excision (TAMIS-TME). 16 , 17 , 18 , 19 Both groups concluded that navigation was feasible and safe, with satisfactory accuracy for clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations